Ultrasonic Measurement of Normal Splenic Size in Infants and Children in Pediatric Indian Population - Tanna , Nita A; Ambiye , M V; Tanna , Vilpa A; Joshi , Himanshu A (National Journal of Community Medicine, 2012)
Background: No two individuals are alike in this world, not even identical twins. In children, knowledge of normal splenic size (splenic length) in relation to age and other biometric parameters (height and weight) of physical growth is of paramount importance for the determination of mild splenomegaly. Objectives: The purpose of this study is to measure normal splenic size in infants & children in Indian population by ultrasonography; to establish correlation of splenic size with age, height and weight. Methods: The present study was conducted in the departments of Anatomy, Radiology and Paediatrics at a General Public Charitable Hospital, Mumbai. The study group consisted of 80 children of both sexes, who were referred to the Radiology department for ultrasonography for abdominal and/or pelvic problems unrelated to the spleen. The splenic length was measured by a radiologist using a commercially available real time ultrasound system with a TOSHIBA ECOCEE USG SYSTEM particularly by using the convex probe. Results: In the present study, p value is less than 0.001 for all - age with splenic size, splenic size with height, splenic size with weight indicate significant correlation of slenic size with age, height and weight. Conclusion: I believe this study shall stand as a good reference to Radiologists and Paediatricians in early diagnosis as well as undiagnosed and complicated disorders involving the spleen.